PEMAHAMAN DASAR DALAM TEORI KLASIK PERTUMBUHAN EKONOMI, PEMBANGUNAN EKONOMI, DAN PENDEKATAN EKONOMI ISLAM - Bagus Hermansyah; M. Rifyal Ali (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This research commences by addressing developmental concerns. Development pertains to the progression and alteration process that leads to enhancement. Each developmental endeavor aims to ameliorate the well-being of the community. Initially, development primarily emphasized the economic advancement of a community, as the success of development was gauged by the substantial economic growth and societal transformation. This study draws upon the development concept that has been deliberated by experts such as Rostow and Lewis. Arthur Lewis's theory explores economic development in both rural and urban settings, while, according to Rostow, economic development and the transition from traditional to modern society encompass multifaceted dimensions. Economic growth stands out as a key macroscopic indicator frequently employed to assess developmental progress. Nevertheless, even though economic growth has served as a developmental benchmark, it remains rather broad in scope and lacks a detailed reflection of individual advancements within society. The aspiration is that regional-level development will also yield favorable consequences for economic growth